Improving Students’ Speaking Ability and Willingness to Communicate through Joining English Debating Community - Afnesha Chang; Asma Alhusna (CV. Multi Kreasi Media, 2022)
This research was conducted to see how students' ability and desire in speaking could be improved by participating in the English debate community. This is done because many of the students have difficulty in speaking activities even though they already know various kinds of vocabulary and sentence structures. This research is a type of literature review research by reading and recording the thoughts of experts from various sources. From the results of this study, it was found that students' English-speaking skills improved in terms of fluency by regularly participating in the English debate community. This happens because by participating in the English debate activities students are forced to speak and think quickly in English and this makes them very accustomed to speaking.